(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This study aims to identify the promotional strategies implemented at SMP Negeri 1 Puring Kencana and SMP Negeri 1 Empanang, to analyze the challenges encountered during their implementation, and to examine the efforts undertaken by both schools to overcome these constraints. This research employed a qualitative descriptive approach conducted at SMP Negeri 1 Puring Kencana and SMP Negeri 1 Empanang. Data were collected through in depth interviews with principals, vice principals for public relations, and teachers, supported by participant observation and document review. Data validity was ensured through source and technique triangulation. The findings reveal that both schools primarily employ banners, brochures, and community-based activities as their initial promotional tools. However, recognizing the limitations of human resources and geographical remoteness, both institutions have increasingly adopted digital media particularly WhatsApp, Facebook, and YouTube to broaden their promotional reach and engage wider audiences. Furthermore, collaboration with nearby elementary schools has proven effective in strengthening student recruitment and building sustainable community relations. These adaptive strategies demonstrate how schools in remote areas creatively utilize low-cost digital platforms and inter-school partnerships to enhance visibility. The study contributes to educational management by providing insights for school administrators, policymakers, and public relations practitioners seeking effective and contextually grounded promotional strategies for resource-limited regions.